Improving nurses' knowledge, attitude, and performance in relation to ethical codes through group reflection strategy - Marzieh Momennasab; Marjan Ghanbari; Mozhgan Rivaz (BMC, 2021)
Abstract Background The most basic responsibility of nurses that even precedes their therapeutic role is respect for professional ethics in providing clinical care. The present study was conducted to determine the effect of group reflection on the knowledge, attitude and performance of nurses in relation to ethical codes. Methods The present blinded, before-after, educational trial was conducted on 86 nurses working at a general hospital in the south of Iran who were randomly divided into a intervention (n = 44) and a control (n = 42) group. Data were collected before and after the intervention using three tools, including a knowledge test, an attitude rating scale and a performance questionnaire. In the intervention group, the intervention given consisted of four sessions of group reflection, and the control group received a single lecture on ethical codes. Results The mean changes in the nurses' score of knowledge after the intervention compared to before differed significantly in both intervention and control groups (P < 0.001), but there was no significant difference between the two groups in terms of the mean changes in the score of knowledge (2.73 ± 3.45 in intervention group vs. 2.57 ± 3.36 in control group, P = 0.83). Although the mean score of attitude differed significantly between the intervention and control groups in the posttest (34.7 ± 8.44 in intervention group vs. 29.95 ± 9.09 in control group, P < 0.014), the two groups were not significantly different in terms of the mean changes in the score of attitude in relation to ethical codes before and after the intervention (P < 0.14). Moreover, the two groups were significantly different in terms of the mean changes in the scores of performance in the two stages (9.07 ± 16.84 in intervention group vs. 0.67 ± 20.01 in control group, P < 0.001). Conclusion Group reflection can improve the knowledge, attitude and performance of nurses in relation to ethical codes. Although lectures can help improve nurses' knowledge and attitude in this area, they have no significant effects on their performance. Trial registration Iranian Registry of Clinical Trials (No: IRCT2016070317546N6, registration date: 10 October 2016), https://www.irct.ir/trial/16112